Calcination conditions and stability of supported Ni4La oxide for catalytic decomposition of N2O. Issue 17 (27th February 2015) - Shen, Yuesong; Li, Chengliang; Tang, Yilong; Zhu, Shemin
<x xml:space="preserve">Abstract</x> A novel catalyst of supported Ni4La oxide calcined at 400 °C in nitrogen completely decomposes N2O at 375 °C.